Template-free anion-controlled synthesis of Pd (II) nano-aggregates for the antifouling polymerization of CO and ethylene - Lim, Yu Na; Chae, Soo Kyung; Yim, Woongbin; Park, Ji Yong; Yoon, Woojin; Yun, Hoseop; Kim, Eunha; Son, Seung Uk; Jang, Hye Young (Applied Organometallic Chemistry, 2019)
The reaction of [(domppp) Pd (OAc) 2 ] [domppp = 1,3-bis (di-o-methoxyphenylphosphino)propane] and imidazolium-functionalized carboxylic acids containing various anions (Br − , PF 6 − , SbF 6 − and BF 4 − ) resulted in the formation of nano-sized Pd (II) aggregates under template-free conditions. The rate of formation of aggregates can be modulated by changing the anion, affecting the rate of polymerization of CO and olefins without fouling. Herein, we describe the analysis of Pd (II) catalysts by dynamic light scattering, atomic force microscopy, X-ray photoelectron spectroscopy and X-ray crystallography, and co- and terpolymerization results including the catalytic activity, and bulk density and molecular weight of polymers.
Keywords: Anion effects; Antifouling; Nano aggregates; Polyketones; Template-free; anion effect; antifouling; Pd (II) nano-aggregates; polyketone; template-free